Choice of coping strategies in adolescence (Actual Problems of Psychology in Educational Institutions, 2022)
The article presents the problem of choosing coping strategies in adolescence. It is determined that it is precisely in youthful age that the problems of moral, existential, professional content, development of reflection significantly affect the emergence, course and experience of the personality of stressful situations. With the help of an empirical study, it was determined which coping statages in adolescence prevail. It has been proved that with age the choice of coping strategies varies.
Keywords: coping strategies; preventive overcoming; peculiarities of choosing coping strategies; youth age